DUALISME PEMBATALAN PERATURAN DAERAH PROVINSI DENGAN PERATURAN PRESIDEN DAN PERATURAN MENTERI DALAM NEGERI - Gde Edi Budiartha (University of Udayana, 2015)
Local regulations are local regulations that are established by local specificities recognized by the Constitution of the Republic of Indonesia-1945 as part of their decentralization. Local regulations can not contradict the legislation of higher order not to cause a result of the cancellation. This cancellation is the authority of the central government in relation to the unitary state. Supervision by the central government there are two models of preventive supervision and oversight repesif. Cancellation regulatory oversight repesif area is conducted on local government. Cancellation Provincial Regulation made by the President and the Minister of the Interior gave rise to a dualism. For it will be discussed on How cancellation arrangements are made with the Provincial Regulations and Regulations Presidential Decree of the Minister of the Interior? 2. What is the legal effect of the cancellation of Provincial Regulation by Presidential Decree and the Regulation of the Minister of the Interior? The issues discussed using normative research by using the approach of legislation, the legal concept analysis approach, in order to obtain answers that dualism cancellation provincial regulations stipulated in several laws including Law No. 32 Year 2004 on Regional Government, Law No. 28 year 2009 on Local Taxes and levies, Government Regulation No. 79 Year 2005 on Guidelines Direction and Control of Local Government, Minister of the Interior No. 1 Year 2014 on the Establishment of the Regional law Products stating that the authority of the cancellation of regulations made by the President of the instrument while the Presidential Decree cancellation made by the Minister of the Interior was limited to cancellation Draft Regional Regulation on stage during the evaluation of preventive supervision and legal consequences caused by the dualism cancellation of local regulations are different between cancellation made by the President and minister of Interior. Cancellation is cancellation of its President in the field of executive interim final cancellation made by the Minister of the Interior if the local government to enforce the local regulations canceled Interior Minister will ask the cancellation to the President.